The factor of the shadow economy in the context of its influence on the socio-economic system of Uzbekistan (International Scientific Journal Alfraganus, 2024)
Uzbekistan is moving into a more complex phase of socio-economic reforms. An important mediumterm task is to ensure the inclusiveness and transparency of reforms. At the same time, a significant amount of theshadow economy hinders the processes of achieving Uzbekistan’s strategic goals. The presence of a shadow economyin Uzbekistan, in our opinion, is a system-forming problem. Even officially, the shadow economy of Uzbekistan isestimated at 48% of the country’s GDP. A high level of shadow turnover remains in the service sector, especially in tradeand public catering, road transport, housing construction and repair, and the provision of accommodation services.Despite the achieved results of the reforms, the republic’s economy remains predominantly not free, which ultimatelycontributes to the departure of entrepreneurs to the shadow sector. Let us single out that the shadow economy inUzbekistan is able to act as a catalyst for social tension in society. To reduce it, it is necessary to help the population towork legally, to interest them in this. It is important to minimize the control functions and powers of ministries anddepartments that contribute to the risks of the shadow economy and corruption,formation in society of a feeling of intolerance towards it, promotion of the prestige of legal business.
Keywords: Uzbekistan, economy, transparency, reform, shadow sector, threat, freedom of business, rating, statistics, post-provision, mayor protivodeistviya